Management komplizierter monochorialer Zwillingsschwangerschaften - Degenhardt, J.; Enzensberger, C.; Tenzer, A.; Kawecki, A.; Kohl, T; Axt-Fliedner, R. (Zeitschrift für Geburtshilfe und Neonatologie, 2015)
Multiple gestation is associated with an increased risk for adverse pregnancy outcome. Monochorionic twins are at risk for complications specific to these pregnancies, such as twin-twin transfusion syndrome (TTTS) or twin reverse arterial perfusion (TRAP) sequence. In this article we give an overview on prenatal diagnosis, treatment and outcome of twin pregnancies complicated by TTTS and TRAP sequence.
Keywords: Monochorionic twins; twin-to-twin transfusion syndrome; TRAP